Anteseden dan Konsekuensi Strategic Human Resource Management (SHRM): Sebuah Usulan Kerangka Kerja Konseptual - Anatan, Lina (Kajian Manajemen dan Bisnis, 2010)
To date, the business environment becomes more and more dynamic, turbulent, and increasingly competitive. Enterprises as business performers require the role of high quality and competent human resources or employees to respond to the development of the business environment. The implementation of good management and investment in human resource are crucial to competitive advantage.